Confirmatory factor analysis of the Brief Resilience Scale for Brazilian athletes - Nogueira-Neves, Angela; Barbosa, Franciele Pires; da Silva, Marcos Paulo Sena; Brandão, Maria Regina Ferreira; Zanetti, Marcelo Callegari (Cuadernos de Psicología del Deporte, 2018)
In general studies of resilience, the traumatic events, stressors and risks tend to be events that astonish the person. In the sports setting, it is not always true, since athletes actively seek for challenging situations. e pressure to perform at a high standard, worries about job security and injury, diculties balancing sport and social life commitments, lack of coach feedback, lack of social support in competition and training are some specic stressor in sports settings. The aim of this study was to adapt cross-culturally and examine the psychometric properties of the Brief Resilience Scale (BRS) for Brazilian athletes. Following the cross-cultural adaptation of the original English scale, data were collected from 330 athletes (18 - 44 years of age) of both sexes. The original model of the scale was tested, with conrmatory factor analysis, using LISREL software (version 8.51). A satisfactory t for the Brazilian model with one factor and six items was found (χ2 = 18.32, p <.001; RMSEA = .07; GFI = .993; AGFI = .97;, NFI = .979; CFI = .993; NNFI = .986; χ2 /Df = 2.61), replicating the original structure of the scale. Satisfactory evidence of construct validity and internal consistency were also generated through analysis of factor loadings, t-values, Cronbach’s alpha, and construct reliability tests. The BRS appears to be a valid and reliable scale to assess resilience among Brazilian athletes.